Suicide attempt and its determinants among youth in central, north, and west Gondar zones, northwest Ethiopia: Findings from the youth health project - Geremew, Alehegn Bishaw; Gelagay, Abebaw Addis; Yeshitila, Hedija Yenus; Azale, Telake; Habitu, Yohannes Aynaw; Abebe, Solomon Mekonnen; Birru, Eshetie Melese; Fentie, Elsa Awoke (Frontiers in Psychiatry, 2023)
Introduction Suicide is a deliberate attempt to take one's own life. Suicidal behavior among adolescents and young people, a significant global public health issue, is under-researched, particularly in developing nations like Ethiopia. Therefore, this study aimed to assess the prevalence of suicide attempts and their determinants among school-aged and out-of-school youth in the central, north, and west Gondar zones of Ethiopia. Methods A community-based cross-sectional study was conducted from 15 March to 15 April 2019, among youth in the central, north, and west Gondar zones. The data for this study were extracted from information collected for the assessment of common health problems and risky behaviors among youth. A multistage cluster sampling technique was used to collect the data using face-to-face interviewer-administered questionnaires. Bivariable and multivariable logistic regression analyses were done to identify the independent determinants of suicide attempts. An adjusted odds ratio (AOR) with a 95% confidence interval (CI) was used to identify the presence and direction of the association between the dependent and independent variables. Results A total of 1,597 youth participated in this study, and the mean age of the participants was 19.1 ± 2.8 standard deviations (SDs). The lifetime prevalence of suicide attempts in the study participants was 5.5% (95% CI: 4.4, 6.8%). Risky sexual practices (AOR = 1.89, 95%CI: 1.19–2.99), the presence of common mental health problems (AOR = 6.31, 95% CI: 3.78–10.88), having a personal income (AOR = 1.68, 95% CI: 1.05–2.71), and a history of violence (AOR = 2.81, 95% CI 1.76–4.49) were significantly associated with a suicide attempt. Conclusion In this study, the prevalence of lifetime suicide attempts among youth is high. The presence of common mental health problems, having a personal income, risky sexual practices, and a history of violence increase the likelihood of suicide attempts. Working on the reduction of risky sexual practices, ensuring the integration of psychological treatment into medical treatment programs for victims of violence, psychosocial support for young people, and integrating youth-friendly health services to promote mental health would help to reduce suicide attempts among youth.